Sleep patterns and school performance of Korean adolescents assessed using a Korean version of the pediatric daytime sleepiness scale - Seonkyeong Rhie; Sihyoung Lee; Kyu Young Chae (Korean Pediatric Society, 2011)
PurposeKorean adolescents have severe nighttime sleep deprivation and daytime sleepiness because of their competitive educational environment. However, daytime sleep patterns and sleepiness have never been studied using age-specific methods, such as the pediatric daytime sleepiness scale (PDSS). We surveyed the daytime sleepiness of Korean adolescents using a Korean translation of the PDSS.MethodsWe distributed the 27-item questionnaire, including the PDSS and questions related to sleep pattern, sleep satisfaction, and emotional state, to 3,370 students in grades 5-12.ResultsThe amount of nighttime sleep decreased significantly with increasing age. During weekday nights, 5-6th graders slept for 7.95±1.05 h, 7-9th graders for 7.57±1.05 h, and 10-12th graders for 5.78±1.13 h. However, the total amounts of combined daytime and nighttime sleep during weekdays were somewhat greater, 8.15±1.12 h for 5-6th graders, 8.17±1.20 h for 7-9th graders, and 6.87±1.40 h for 10-12th graders. PDSS scores increased with age, 11.89±5.56 for 5-6th graders, 16.57±5.57 for 7-9th graders, and 17.71±5.24 for 10-12th graders. Higher PDSS scores were positively correlated with poor school performance and emotional instability.ConclusionKorean teenagers sleep to an unusual extent during the day because of nighttime sleep deprivation. This negatively affects school performance and emotional stability. A Korean translation of the PDSS was effective in evaluating the severity of daytime sleepiness and assessing the emotional state and school performance of Korean teenagers.